If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -4 = 2t + -2 Reorder the terms: -4 + 4t = 2t + -2 Reorder the terms: -4 + 4t = -2 + 2t Solving -4 + 4t = -2 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. -4 + 4t + -2t = -2 + 2t + -2t Combine like terms: 4t + -2t = 2t -4 + 2t = -2 + 2t + -2t Combine like terms: 2t + -2t = 0 -4 + 2t = -2 + 0 -4 + 2t = -2 Add '4' to each side of the equation. -4 + 4 + 2t = -2 + 4 Combine like terms: -4 + 4 = 0 0 + 2t = -2 + 4 2t = -2 + 4 Combine like terms: -2 + 4 = 2 2t = 2 Divide each side by '2'. t = 1 Simplifying t = 1
| 3a-12=6a-21 | | 8k+8(k-1)=5k+36 | | 13x-7x-35=6x-35 | | 2a+14=5a+5 | | Y=x^2-9x+8 | | 2g+14+5g-8g=3+8 | | 6t+12=18 | | 7(1-3n)-2n=-85 | | 5y^2-12y+5=0 | | 2g+14+5g-8g=3-8 | | (6x+2)(x-3)=0 | | 3w-8=7w | | y=0.5+b | | 2*x^3-3*x^2-72*x+3=0 | | 7p+4=67 | | 6r+9=63 | | t^2(t^2-5)=2t^2-5 | | 6x+1y=30 | | (2r+2r)=96 | | 3r-5=0 | | 12+14=-7(x-4)+8x | | 0.36y=1 | | 3x+17=74 | | -2x+8=x+29 | | 2+4x=-4-2x | | log^5(3-x)=5 | | -7*(x-4)+8x=12+14 | | -9-4=6x+2-5x | | x^2=2.8 | | 5x^2-10x+7-4x-14x^2= | | 39x=6 | | 36x^4-16y^2=0 |